Caleb's Story - Maclachlan, Patricia (New York Joanna Cotler Book, 2001)
The stranger lurking on the witting family's prairie farm turns out to be their long-lost grandfather, whose presence plus prodding from caleb forces jacob to deal with his past
American Corner
11
Keywords: English Fiction; English Stories